2014
DOI: 10.1002/anie.201400793
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylations of Alkenes with CO Surrogates

Abstract: Alkene carbonylation reactions are important for the production of value-added bulk and fine chemicals. Nowadays, all industrial carbonylation processes make use of highly toxic and flammable carbon monoxide. In fact, these properties impede the wider use of carbonylation reactions in industry and academia. Hence, performing carbonylations without the use of CO is highly desired and will contribute to the further advancement of sustainable chemistry. Although the use of carbon monoxide surrogates in alkene car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
124
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(129 citation statements)
references
References 90 publications
1
124
0
4
Order By: Relevance
“…Its use has thus attracted a lot of interest in many fields of chemistry from the most fundamental researches to the most applied one [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However it is also a very thermodynamically stable molecule and only in few cases the balance between the cost of the required energy input (physical or chemical energy) and the created value of the product is economically favorable [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Its use has thus attracted a lot of interest in many fields of chemistry from the most fundamental researches to the most applied one [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. However it is also a very thermodynamically stable molecule and only in few cases the balance between the cost of the required energy input (physical or chemical energy) and the created value of the product is economically favorable [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…Among the application of catalytic reaction for development of sustainable organic processes, the catalytic carbonylation reaction [ 23 ] and hydroformylation [ 24 -27 ] must be highlighted since it represent the major technology for the production of value-added bulk and fine chemicals from olefins [ 28 ]. For example, methyl propionate, the monomer of polymethacrylates, is produced on the scale of > 300000 tons per year via palladium-catalyzed methoxycarbonylation of ethylene and over 10 million tons of oxo products are produced every year through hydroformylation of alkenes [29].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, many research groups have worked on the development of CO surrogates that generate CO in situ, and several safe and facile carbonylation reactions using CO surrogates have been reported. [11][12][13][14][15][16][17][18] Recently, we and Tsuji et al independently reported Pd-catalyzed carbonylation reactions using a liquid CO surrogate, phenyl formate. It was found to react with weak bases (e.g., NEt 3 ) at elevated temperatures to form CO and phenol, and could be employed in external-CO-free carbonylation reactions in situ.…”
mentioning
confidence: 99%